Solving Fuzzy Bottleneck Transportation Problems Using Blocking Zero Point Method - Dr. S.Kumaraghuru, S.Naresh kumar (International Journal of Scientific Research and Management (IJSRM), 2015)
Transportation Problem is a well known topic and is used very often in solving problems of management science. This paper analyzes the Blocking Method for finding an optimal solution to Fuzzy Bottleneck Transportation Problems which is very different from other methods. And also finding the efficient solutions of Fuzzy Bottleneck Transportation Problems by using Blocking Zero Point Method. A numerical example is given to show the efficiency of the method.